2004
DOI: 10.1002/er.969
|View full text |Cite
|
Sign up to set email alerts
|

Natural vacuum distillation technique—Part II: Experimental investigation

Abstract: SUMMARYThis part of the study is concerned with the experimental investigation and uncertainty analysis of natural vacuum distillation process. Natural vacuum distillation (NVD) system is operated in the forms of free and forced mass convection. The experiments are conducted at temperatures of 20 and 408C of network water as fluid in the system. During the experiments, total pressure losses are measured as 15.33 kPa during free mass convection distillation while 14 kPa during forced mass convection distillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It can be noted thay the concept of barometric distillation has originated by Bemporad [19]. Al-Kharabsheh then developed a workable configuration through both theoretical and experimental studies [20,21]. Middilli and Ayhan also presented theoretical and experimental concepts for both natural draft condensation and forced condensation in two different studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted thay the concept of barometric distillation has originated by Bemporad [19]. Al-Kharabsheh then developed a workable configuration through both theoretical and experimental studies [20,21]. Middilli and Ayhan also presented theoretical and experimental concepts for both natural draft condensation and forced condensation in two different studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the production rate is lower than the theoretical model predicts. The theoretical and practical experiments yielded maximal freshwater production rates of 9.79 and 3.96 kg/h, respectively [10]. The experimental set-up used almost three times the amount of power predicted by the theoretical study.…”
Section: Introductionmentioning
confidence: 93%
“…The model was created with solar energy in mind. Midilli and Ayhan [10] built an experimental system based on the design provided by the theoretical model. Free and forced mass convection were used in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…There were two variations in design, one was that they installed a 3 kW fan to draw vapors from evaporator to condenser chamber and other was their evaporator area was 0.16 m 2 . After doing a thermodynamic analysis with and without fan in operation, an experimental setup was built in 2007 [8]. The maximum fresh water production rates was 3.96 and 7.79 kg per hour measured experimentally and theoretically, respectively.…”
Section: Direct Evaporation Type Barometricmentioning
confidence: 99%